Competency Level of Engineering Graduates and Quality of Engineering Education in Nepal - Pahari, Bharat R. (Journal of the Institute of Engineering, 2009)
This study is the part of the outcome of the research work on quality of engineering education in Nepal. Some 246 respondents among the stakeholders of engineering education were referred in this research. In the course of time, the pace of development of the engineering education is appreciable. However, there are the voices from different stakeholders that the existing level of graduating engineers from Nepal are not meeting the standard demanded by the market. In the course of time, pressure has been intensified to respond this in prevailing education system. This has developed concern over the competency parameters as the tools of quality in engineering higher education. This study, therefore is an attempt to explore the competency level of the graduating engineers of Nepal. In this study, some prominent competency parameters influencing quality of engineering education were identified. Key words: competency, quality, engineering education, graduating engineers etc. Journal of the Institute of Engineering, Vol. 7, No. 1, July, 2009 pp. 65-75 doi: 10.3126/jie.v7i1.2064